Influences of relative humidities and temperatures on the collection of C2-C5 aliphatic hydrocarbons with multi-bed (Tenax TA, Carbograph 1TD, Carboxen 1003) sorbent tube method. (February 2017) - Ho, Steven Sai Hang; Chow, Judith C.; Watson, John G.; Wang, Liqin; Qu, Linli; Dai, Wenting; Huang, Yu; Cao, Junji
Abstract: Volatile organic compounds (VOCs) are measured with sorbent tubes followed by thermal desorption (TD) analysis. Water vapor in the atmosphere affects sampling breakthrough and results in low collection efficiency. This paper reports the effect of relative humidity (RH) and temperature on the collection of 57 ozone precursors with a multi-bed tube composed of three different strengths of adsorbents (Tenax TA, Carbograph 1 TD, and Carboxen 1003). Unacceptable breakthrough values for volatile C2 -C5 aliphatic compounds were observed under high (>60%) RHs. The breakthrough volumes (BV) for C2 aliphatic compounds were reduced 13–22 fold under 90% RH. Dry-purge with inert helium gas removes excessive water content before the TD analysis but also causes a maximum of 40% loss of target analytes. Condensation is another pathway for water retention. The tube temperature should be regulated at 5–10 °C above the air temperature to minimize condensation under RHs >30%. Highlights: Water vapor in the atmosphere affects VOCs sampling breakthrough with sorbent tube method. High relative humidities lead low collection efficiency for volatile C2 -C5 aliphatic hydrocarbons. Dry-purge removes excessive water content but also causes loss of target analytes. Optimizes the tube temperature (∼5–10 °C above ambient temperature) in order to reduce water condensation during sampling.